Kesejahteraan Karyawan Perspektif Maqashid Syariah Pada Pusat Penelitian Kopi dan Kakao - Rohma Vihana Enggardini; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this study is to determine the economic impact in improving the welfare of employees Coffee and Cocoa Research Center Indonesia when viewed through the perspective of maqashid sharia. The method used is a qualitative approach, a strategy case studies and descriptive analysis techniques are collecting data through interviews and observations of informants. Informants are employees working at the Coffee and Cocoa Research Center Indonesia amounting to nine people. The Results from this study is economic impact and fulfillment of welfare for employees at the Coffee and Cocoa Research Center still ranks necessities. Five indicators used in this study is maqashid syariah can be met by almost all employees. The economic impact can be seen, among others, the changes experienced by the employee, the changes are seen from the increased monthly income,expenditure control, insufficient subsistence, and increasing assets and preparation for future family prepared before retirement arrives.